Major Challenges and Prospects of Sustainable and Inclusive Growth in India - Ujjal Sut (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2018)
The concept of inclusiveness has gained much importance in the recent years. It is one of the widely discussed subject matter globally. Inclusive growth is a concept that ensures equitable opportunities for economic participants during economic growth with benefits incurred by every section of society. India is committed for inclusive growth. The agenda of inclusive growth was envisaged in the Eleventh and Twelfth five year plans. The basic themes of the Eleventh and twelfth five year plans were “Inclusive growth” and “Faster , Sustainable and more Inclusive growth” respectively. The present paper tries to give a broad overview of the concept of inclusive growth, highlighting the issues and challenges that need to be addressed for making inclusive growth , an effective tool for economic empowerment of India .